Self Efficacy And The Quality Of Life Of Schizophrenia Caregivers - Mulyanti Ners; Brune Indah Yulitasari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Self efficacy is an important factor to improve the quality of life of Schizophrenia caregivers. A caregiver’s quality of life affects treatment process which is an important key in curing Schizophrenia patient. This research aims to investigate the relation of self-efficacy to the quality of life.  This is a quantitative research with cross sectional approach. The research was conducted in the working area of Puskesmas Godean I, i.e. Desa Sidoluhur, Desa Sidoagung, Desa Sidomulyo, and Desa Sidomoyo on August 1 to September 15, 2018. There were 47 participants chosen using consecutive sampling technique. The dependent variable is the quality of life of Schizophrenia caregivers. Meanwhile, the independent variable is self-efficacy. Both variables were measured through questionnaire. The quantitative data was analyzed using chi square test. The characteristics of the research subjects are: female, middle aged, married, low-income earners, senior high school graduates, and have caring experience of more than 5 years. It is found that the self-efficacy of schizophrenia caregivers is in ‘strong’ category. There is a significant relation between the self-efficacy of Schizophrenia caregivers and their quality of life. The quality of life of Schizophrenia caregivers is influenced by high level of self-efficacy.